Quintuple Helix Synergy Driving Palm Sugar MSMES’ Competitiveness For Sustainable Development Goals (SDGS) - Mustika Dewi; Syukron Firdaus Siregar; Mhd Harry Azhari As’ad (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This study investigates the contribution of the quintuple helix collaboration—comprising academia, industry, government, communities, and media—in enhancing the competitiveness of coconut sugar micro, small, and medium enterprises (MSMEs) and advancing the Sustainable Development Goals (SDGs). The research develops an innovation-oriented collaboration framework designed to strengthen MSME competitive capacity and promote sustainable rural transformation. Employing a sequential mixed-methods approach, quantitative analysis was conducted on 100 coconut sugar MSMEs in South Tapanuli using Structural Equation Modelling (SEM-AMOS), complemented by qualitative insights from in-depth interviews with key helix actors. The results demonstrate that quintuple-helix interactions have a significant direct effect on competitive advantage (? = 0.412, p 0.05) and an indirect effect through innovation capabilities that enable sensing, seizing, and transforming market opportunities. The study’s novelty lies in integrating the quintuple helix perspective with innovation strategy to construct an inclusive, sustainability-oriented model for export-driven MSMEs. The findings provide strategic implications for policy design, emphasizing supply-chain integration, institutional capacity building, and digital marketing strategies to enhance MSME performance and accelerate progress toward SDG 8: Decent Work and Economic Growth.